Taxation and Development. A Capacities Approach - López Castellano, Fernando (Advances in Social Sciences Research Journal, 2018)
The principal objective of this paper is to show that taxation is a crucial element of good governance and the legitimacy of the State and of the citizen's commitment with politics, and, finally, of development. Assuming that “social heritage” as regards education, health and collective contributions largely explains differences in income at an international level, we investigate the relationships between State and society in terms of taxation and we conclude with the importance of the tax system in the formation of the state and in the adoption of development strategies. In this paper Sen’s approach of capacities is adopted, emphasizing the constitutive role of institutions, and it is assumed that the latter must perform the function of development of human capabilities. In Sen’s concept of development, Gross Domestic Product (GDP) growth is seen as a means of expanding the fundamental freedoms enjoyed by members of the society. These freedoms depend on social and economic institutions (health and education) and on political and human rights (freedom of political participation). In addition, it starts out from the idea that institutions, besides defining the framework of action of human beings in the social sphere, can shape their behaviour, by changes in values. In this sense, social policy must be placed at the same level as economic policy to ensure a balanced and sustained development. Therefore the tax system is shaped as an institution fundamental to the definition of State capacity and of development policy, and as a key element of institutional quality, because it generates the resources to create institutions of a high standard, and contributes to the establishment of a closer relationship between the State and the citizen. The Political Economy of taxation provides a good interpretative framework for the creation of the State in undeveloped countries to propose a fiscal agenda for development. The paper is organized as follows. After a brief introduction, Section 2 addresses the mounting literature on State building. Section 3 studies the relationship between state capacity and development. Finally, Section 4 proposes a tax reform for development.